Memahami Tanda Rofa’ Dommah dan Hikmahnya untuk Mewujudkan Kehidupan yang Lebih Baik - Annisa Harahap; Fadhilatul Husna; M.Rifqi Fauzi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Understanding nahwu, particularly the grammatical marker raf‘ in the form of ḍammah, is essential for accurately analyzing the structure of Arabic sentences. Ḍammah serves as a marker for the marfū‘ grammatical case in both nouns (ism) and verbs (fi‘l) under specific conditions. Mastery of this aspect is not only beneficial for academic or religious purposes but also offers valuable life lessons. Values such as precision in thinking, carefulness in speech, and clarity in communication are among the wisdoms that can be gained. In practice, understanding the raf‘ sign ḍammah teaches individuals to be more thoughtful in language use and more sensitive to meaning. Beyond improving one’s Arabic language skills, it also fosters a logical and organized mindset. Therefore, learning about the raf‘ sign ḍammah contributes to the development of a disciplined, responsible, and ethical character, both in social, educational, and spiritual contexts.